Application of Rotational Thromboelastometry in Patients with Acute Promyelocytic Leukemia. (August 2022) - Sabljic, Nikica; Pantic, Nikola; Virijevic, Marijana; Bukumiric, Zoran; Novakovic, Tina; Pravdic, Zlatko; Rajic, Jovan; Vidovic, Ana; Suvajdzic, Nada; Jaradeh, Mark; Fareed, Jawed; Antic, Darko; et al.
Introduction: Hemorrhagic early death (HED) remains a major cause of treatment failure among patients with acute promyelocytic leukemia (APL). We aimed to investigate the prognostic potential of rotational thromboelastometry (ROTEM) for bleeding in patients with APL. Materials and Methods: 31 newly-diagnosed APL patients (median age of 40 years; 14 female/17 male) that underwent treatment at the Clinic of Hematology UCCS from 2016-2020 with all-trans retinoic acid and anthracyclines were recruited. CBCs (complete blood count), conventional coagulation tests (CCTs), and ROTEM parameters obtained before treatment initiation were evaluated. Results: All patients demonstrated at least one ROTEM parameter out of the reference range. ROTEM parameters associated with significant hemorrhage were EXTEM clotting time (CT) (P = 0.041) and INTEM amplitude 10 (A10) (P = 0.039), however, only EXTEM CT (P = 0.036) was associated with HED. Among CBCs and CCTs, only platelets were associated with significant bleeding (P = 0.015), while D-dimer was associated with both bleeding and HED (P = 0.001 and P = 0.002, respectively). Conclusion: Our results indicate that ROTEM parameters may reveal hypocoagulability in APL patients and have the potential to improve current hemorrhage prognostic methods. Additionally, these results suggest the combination of ROTEM and CCTs might be useful in identifying patients at risk for HED.